Corruption - Brioschi, Carlo Alberto (Brookings Institution Press, 2017)
"From ancient times to modern, corruption has been ingrained in human society and is still a powerful issue in the contemporary world. In Corruption: A Short History, Carlo Brioschi provides a thorough and entertaining look at how corruption was born and has evolved over time, without ever being stamped out. He examines corruption through politics and history-from Babylon to modern-day U.S. organized crime and the great market collapses-and concludes with reflections on the moral perception of corruption and its dangers for democracy"--